Developing an animal-assisted support program for healthcare employees - Bella Etingen; Rachael N. Martinez; Bridget M. Smith; Timothy P. Hogan; Laura Miller; Karen L. Saban; Dawn Irvin; Becky Jankowski; Frances M. Weaver (BMC, 2020)
Abstract Background Employee burnout and its associated consequences is a significant problem in the healthcare workforce. Workplace animal therapy programs offer a potential strategy for improving employee well-being; however, research on animal therapy programs for healthcare workers is lacking. This study aimed to evaluate the feasibility, acceptability and preliminary impact of an animal-assisted support program to improve healthcare employee well-being. Methods In this mixed-methods pilot intervention study, we implemented an animal-assisted support program in a multidisciplinary healthcare clinic at a large VA hospital. The program included 20 sessions over 3 months, each approximately 1-h long. Real-time mood data were collected from participants immediately before and after each session. Participation rates were tracked in real time and self-reported at follow-up. Data on burnout and employee perceptions of the program were collected upon completion via a survey and semi-structured interviews. Differences in mood and burnout pre/post program participation were assessed with t-tests. Results Participation was high; about 51% of clinic employees (n = 39) participated in any given session, averaging participation in 9/20 sessions. Mood (on a scale of 1 = worst to 5 = best mood) significantly improved from immediately before employees interacted with therapy dogs (M = 2.9) to immediately after (M = 4.5) (p = 0.000). Employees reported significantly lower levels of patient-related burnout (e.g., how much exhaustion at work relates to interaction with patients) after (M = 18.0 vs. before, M = 40.0) participating (p = 0.002). Qualitative findings suggested that employees were highly satisfied with the program, noticed an improved clinic atmosphere, and experienced a reduction in stress and boost in mood. Conclusions Establishing an animal-assisted support program for employees in a busy healthcare clinic is feasible and acceptable. Our pilot data suggest that animal-assisted programs could be a means to boost mood and decrease facets of burnout among healthcare employees.